Triangular Collaboration: Strengthening Financing For Sustainable Development Goals - Komara, Syifa Rachmania; Rusliadi, Rusliadi (Universitas Muhammadiyah Makassar, 2024)
The achievement of the Sustainable Development Goals (SDGs) is imperative for global sustainability, necessitating innovative financing strategies that leverage collaboration among government entities, the private sector, and philanthropic organizations. This research explores the framework of triangular collaboration as a means to enhance funding for SDGs, addressing the complex financial landscape that currently hampers effective implementation. Utilizing a qualitative approach, the study conducts in-depth analyses of existing partnerships through multiple case studies to identify best practices and challenges in mobilizing diverse funding sources. The findings reveal that multi-stakeholder engagement fosters synergies, increases resource allocation efficiency, and drives sustainable development. Furthermore, the research highlights critical policy implications, suggesting that coherent governance frameworks and incentives can optimize collaboration among stakeholders. Recommendations include developing tailored funding models that leverage the strengths of each partner. Ultimately, this research contributes to a nuanced understanding of how triangular partnerships can be effectively utilized to address the financing needs of the SDGs while recognizing inherent limitations and challenges in these collaborations.